2023
DOI: 10.33494/nzjfs532023x218x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral quality influence on in vitro morphophysiological responses of Eucalyptus dunnii Maiden and Eucalyptus grandis W.Hill ex Maiden × E. urophylla S.T.Blake

Abstract: Background: In vitro growth and development of plants in the micropropagation stages are influenced by several factors, including the light spectral quality, which has shown important effects on the photomorphogenesis. The work aimed to evaluate the photomorphogenic effect of spectral qualities on in vitro culture of Eucalyptus dunnii and Eucalyptus grandis × E. urophylla. Methods: Six light spectral qualities (i.e., red, white, blue, yellow, purple, and green) on in vitro multiplication, elongation, and adven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Also, blue, white, puple and red light increased stomatal densities. Moreover, the study suggests that irrespective of light spectra, E. dunnii showed decreased adventitious rooting [94]. An another similar study on E. grandis × E. urophylla clone was carried out to assess the impact of five different light sources including fluorescent lamp, blue, green, red and yellow cellophane light in bioreactor system.…”
Section: Effects Of Radiation and Light Exposurementioning
confidence: 99%
“…Also, blue, white, puple and red light increased stomatal densities. Moreover, the study suggests that irrespective of light spectra, E. dunnii showed decreased adventitious rooting [94]. An another similar study on E. grandis × E. urophylla clone was carried out to assess the impact of five different light sources including fluorescent lamp, blue, green, red and yellow cellophane light in bioreactor system.…”
Section: Effects Of Radiation and Light Exposurementioning
confidence: 99%
“…Also, blue, white, purple, and red light increased stomatal densities. Moreover, a previous study revealed that irrespective of light spectra, E. dunnii showed decreased adventitious rooting [96]. Another similar study on E. grandis × E. urophylla clone was carried out to assess the impact of five different light sources, namely fluorescent lamps as well as blue, green, red, and yellow cellophane light in a bioreactor system.…”
Section: Effects Of Radiation and Light Exposurementioning
confidence: 99%